Species of Epichlorops Becker from China (Diptera, Chloropidae) - Cui, Yusi; Yang, Ding (Zootaxa, 2009)
The genus Epichlorops Becker was known to distribute only in the Holarctic Region. Here it is recorded from the Oriental Region and also from China for the first time. One new species, Epichlorops yunnanenis sp. nov., is described from Oriental China. One species, Epichlorops puncticollis (Zetterstedt), is newly recorded from Palaearctic China. A key to the species of the genus from China is presented.